2009
DOI: 10.1007/s10493-009-9239-1
|View full text |Cite
|
Sign up to set email alerts
|

Candidate predators for biological control of the poultry red mite Dermanyssus gallinae

Abstract: The poultry red mite, Dermanyssus gallinae, is currently a significant pest in the poultry industry in Europe. Biological control by the introduction of predatory mites is one of the various options for controlling poultry red mites. Here, we present the first results of an attempt to identify potential predators by surveying the mite fauna of European starling (Sturnus vulgaris) nests, by assessing their ability to feed on poultry red mites and by testing for their inability to extract blood from bird hosts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…and that the breeding success of individual birds strongly depends on the presence of predatory mites that attack Dermanyssus spp. (Lesna et al 2009). The only ground nesting group extensively analysed here are the larks (Alaudidae) and these bird species appear to stand out as the only ones that had no Dermanyssus individuals in their nests (Fig.…”
Section: Role Of the Ecosystem In The Nest Environmentmentioning
confidence: 99%
“…and that the breeding success of individual birds strongly depends on the presence of predatory mites that attack Dermanyssus spp. (Lesna et al 2009). The only ground nesting group extensively analysed here are the larks (Alaudidae) and these bird species appear to stand out as the only ones that had no Dermanyssus individuals in their nests (Fig.…”
Section: Role Of the Ecosystem In The Nest Environmentmentioning
confidence: 99%
“…the nest material and its immediate surroundings. Nests usually harbour communities of arthropods, including not only parasites, but also microbivores and predators that feed on them (Fenda 2010; Lesna et al 2009 and references therein). Such communities may harbour several species that are specialized on life in a nest (nidicoles), and they emerge more easily in nests that are re-used by the nesting bird or mammal.…”
Section: Introductionmentioning
confidence: 99%
“…Evans & Till 1966;Domrow 1980). If the mite identified as Hypoaspis fenilis by Hill and Gordon (1945) was Androlaelaps casalis, it is very unlikely that it was the cause of the reported dermatitis, as it has been shown that A. casalis is a predator (Hughes 1976) and does not bite humans (McKinley 1963;Lesna et al 2009). Hill and Gordon (1945) considered it probable that either Haemogamasus oudemansi or Hyposapis fenilis or both were responsible for the dermatitis they observed, but were careful to point out that their evidence was not conclusive.…”
Section: Discussionmentioning
confidence: 99%